(untitled) (Research, Society and Development, 2019)
Reading habit is an important thing for people’s life. Through reading, people are getting information and knowledge that could change their attitude, behavior, or other new things. This study aimed to know the index on students’ reading interest and the factors that influenced the reading interest. Using questionnaire based on Motivation for Reading Questionnaire, the researcher collected the data. The participants were students of 6th, 9th, and 12th grade in Probolinggo. The result showed that students’ reading interest was based on the amount of book they have read. Moreover, the factor was influenced by activity, involvement, and motivation on reading.